Implementasi Literasi dalam Pembelajaran di Kelas V SD Negeri 1 Kota Bengkulu - Twenty Agustiola, Agnes; Trianto, Agus; Ariesta, Ria (UNIB Press, 2025)
Abstract This study aims to determine the implementation of literacy in learning in class V SD Negeri 1 Bengkulu City. The method used in this research is descriptive method with a qualitative approach. The subjects in this study were teachers and students in VA and VB classes who were carrying out thematic learning. This study collected data using observation and recording techniques. Data collection techniques used observation and recording. The data analysis techniques used consisted of data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of literacy in learning in class V SD Negeri 1 Bengkulu City has basic literacy, namely cultural and civic literacy, literacy, financial literacy, and scientific literacy. Teachers and students carry out language skills activities in the form of reading, writing, listening, speaking activities accompanied by thought processes (literacy). Implementation of literacy in learning in class V SD Negeri 1 Bengkulu City is still relatively low. The teacher not only guides and teaches students on cognitive abilities but fosters affective abilities from an early age in elementary school students.Keyword: the problematics of listening to drama, teaching and learning activities. Keyword: Implementation of Literacy, Basic Literacy, Language Acquisition